Molecular interaction study on a new application of ionic liquids as dissolver toward carbonate scale - Muhammad Suhaimi Man,; Teo, Alvin Hua Huang; Syamsul Abdullah,; Hanida Abdul Aziz,; Mohd Hasbi Ab Rahim,; Saifful Kamaluddin Muzakir,; Norwahyu Jusoh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Latest advances of ionic liquids (ILs) have allowed to a new application on the dissolution of calcium carbonate (CaCO3) scales where the CaCO3 scale deposition have seriously severe threat in the petroleum field. In this study, the molecular interaction between CaCO3 and ILs n-pyridinium chloride [NPy][Cl] was studied experimentally in order to get a better understanding during the dissolution of scale. NMR and FTIR spectroscopy was used to study the molecular interaction between CaCO3 and [NPy][Cl] solution during the dissolution process. To further evaluate the result, the simulation study using Gaussian software was utilized to predict in detail the molecular interaction between [Npy][Cl] and CaCO3. The finding from this study showed that the metal complex was formed via ligand after dissolution scale process. Based on the findings, it can be clinched that [Npy][Cl] has potential to be used as a scale dissolver in the oilfield, especially in dissolving calcium carbonate scales.